Rola cara Piotra (927-969) w życiu bułgarskiego Kościoła. Kilka uwag - Leszka, Mirosław J. (Vox Patrum, 2018)
Tsar Peter was a ruler who was active in the sphere of church policy, and is pictured to have been a deep believer himself. He is credited with the fact of granting the title of patriarch to the Bulgarian archbishop, which most probably occurred under the framework of the agreement of 927 (?933/934). The act symbolically completed the process of acquiring full maturity and independence by the Church of Bulgaria. Peter, as the first Bulgarian ruler, had to face a serious problem of heresy. Being fully aware of responsibility for orthodoxy of his subjects’ creed, he was determined enough to take precautions in order to stifle the development of the Bogomil heresy. However, his actual actions (except for his consulting the patriarch) and their results are impossible to pinpoint. On the other hand, it should be stressed that, during the rule of tsar Peter, the Bulgarian monasticism lived through a period of considerable development. The tsar contributed to that progress, though, unfortunately, details of the phenomenon are impossible to determine. Peter himself became a monk before his death, and subsequently his personal worship evolved around his involvement in the monastic movement.